Ketergantungan Penggunaan GoFood terhadap Pola Konsumsi Anak Kost - Afifah Yolanda Dinata; Agus Krisdayanti Pasaribu; Alvarel Sinurat (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid growth of digital food delivery services has significantly transformed the consumption patterns of university students living in boarding houses. This study aims to examine the factors driving dependence on GoFood usage and its impact on the consumption behavior of boarding house students. A qualitative approach was employed, with data collected through online interviews using Google Forms involving students living in boarding houses. The data were analyzed thematically to identify patterns related to usage motives and perceived impacts. The findings indicate that limited personal transportation, attractive promotions, and service practicality are the primary factors contributing to GoFood dependency. The impacts include increased consumptive behavior, reduced social interaction, and changes in eating patterns that tend to be irregular. This study contributes empirical insights into the implications of digital food delivery services on student lifestyles and consumption patterns.